Impact of COVID-19 on food waste behaviour of families: Results from household waste composition audits. (August 2022) - Laila, Amar; von Massow, Mike; Bain, Maggie; Parizeau, Kate; Haines, Jess
Abstract: Objective: The COVID-19 pandemic changed consumers' purchasing and cooking behaviours, which may have resulted in changes in food waste. This study aimed to assess the impact of COVID-19 on household food waste, as well as on purchasing, cooking, and food waste-related perceptions and behaviours among 19 households in Guelph, ON, Canada. Methods: Four-week food waste audits and online surveys were conducted in February–March 2020 (pre-COVID-19) and in July–August 2020 (post-COVID-19). Qualitative interviews were also conducted post-COVID-19 to explore participants' perceptions of household food changes due to COVID-19. Food waste results were analyzed using paired t -test, while survey results pre- and post-COVID-19 were analyzed using the Wilcoxon signed-rank test. Results: While per capita food waste did not significantly change (mean pre  = 1.076 kg per week, mean post  = 1.080 kg per week), total per capita unavoidable food waste (mean pre  = 0.388 kg per week, mean post  = 0.614 kg per week) and pre capita unavoidable fruit and vegetable (mean pre  = 0.289 kg per week, mean post  = 0.427 kg per week) waste significantly increased (p < 0.01) at post-COVID-19. Total per capita avoidable other waste decreased (mean pre  = 0.385 kg per week, mean post  = 0.179 kg per week, p < 0.05). The increase in unavoidable food waste may relate to households cooking more often at home, as reported in interviews, or shopping less frequently and buying more per trip, as identified in the surveys. The decrease in avoidable food waste could be related to the increase in serving of leftovers (p < 0.01), as identified in the surveys, or an increase in meal planning and inventory management, as reported in interviews. Conclusion: Future studies should investigate whether food waste-related changes in behaviour remain after the pandemic as well as any factors associated with maintaining of these behaviours. Interventions may be an opportunity to help households maintain these changes. Highlights: The COVID-19 pandemic has caused changes in consumers' purchasing and cooking behaviours. Our detailed waste audits pre and post-COVID-19 offer an objective measure of household food waste changes. Only per capita avoidable food waste decreased and per capita unavoidable food waste increased from pre to post-COVID-19. COVID-19 pandemic led to changes in household food waste among families in Canada.